Method for producing porous carbon material derived from waste paper
A one-step microwave irradiation process for carbonizing and activating waste paper addresses the inefficiencies of traditional methods, producing a porous carbon body with enhanced properties and economic benefits.
Patent Information
- Application Number
- KR1020240155393
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-11-09
- Filing Date
- 2024-11-05
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2044-11-05
AI Technical Summary
Existing carbonization and activation technologies for producing activated carbon from waste paper are energy-intensive, time-consuming, and require precise control, while microwave-induced carbonization faces challenges due to low precursor absorption, necessitating additional processes that prolong the overall duration and energy consumption.
A one-step microwave irradiation process is employed to carbonize and activate waste paper, using a sealed container setup with a carbon-based material to enhance microwave absorption, thereby simplifying the process and improving efficiency.
This method results in a porous carbon body with excellent physical properties, enabling efficient recycling of waste paper and reducing environmental impact, while offering improved process economics and energy efficiency.
Smart Images

Figure 112024121344443-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing a porous carbon body derived from waste paper, and more specifically, to a method for manufacturing a porous carbon body derived from waste paper by carbonizing and activating waste paper in a one-step process by irradiating it with microwaves. Background Technology
[0002] As the global population continues to grow, the demand and production of various types of paper, such as office paper, newspapers, and cardboard, have also increased. According to previous studies, paper makes up about one-fifth of household waste, and the amount of waste paper generated per household exceeds 4 kg per week. Consequently, recycling or reusing paper is the most practical solution for reducing waste paper generation; however, a problem arises where the pulp fibers of waste paper become too short after a certain recycling cycle, rendering it unsuitable for further papermaking. Nevertheless, because waste paper contains a high amount of lignocellulose, an organic component of plant cells, numerous studies are being conducted to convert waste paper into materials such as cellulose nanofibers.
[0003] The synthesis of carbon materials from lignocellulose precursors, such as waste paper, is receiving significant attention due to cost-effectiveness, the large specific surface area of the carbon materials, excellent electrical conductivity, and physical and chemical stability. Leveraging these unique properties, research on the development and characterization of carbon materials derived from waste paper and biomass has been conducted for applications in energy storage and environmental improvement.
[0004] The production of activated carbon generally proceeds as a two-stage process, involving a carbonization step such as pyrolysis or hydrothermal carbonization, followed by a physical or chemical activation step. However, existing carbonization and activation technologies have limitations, such as high energy, cost, and time consumption, and the need for precise control of activation process requirements like temperature and processing time. Therefore, there is a need to develop a simpler and more sustainable method for manufacturing activated carbon.
[0005] Recently, microwave-induced carbonization technology has been studied as a potential technology for producing porous carbon materials. This is because microwave-induced carbonization technology offers the advantage of reducing processing time and saving energy compared to conventional carbonization methods by promoting volumetric heating. Furthermore, since microwaves interact directly with the internal particles of the activated carbon raw material, they prevent the formation of thermal gradients, enabling the production of more uniform carbon materials. However, microwave-induced carbonization technology has faced limitations due to the low microwave absorption of precursors such as waste paper and biomass. Consequently, there was a disadvantage requiring an additional pre-carbonization process to improve microwave absorption. This pre-carbonization process presented problems such as extending the overall process duration and consuming a significant amount of energy.
[0006] Accordingly, the inventors have completed the present invention by researching a method to synthesize a waste paper-derived porous carbon body in a single step from waste paper without undergoing multiple carbonization and activation steps. Prior art literature
[0007] Korean Registered Patent Publication KR 10-1316565 The problem to be solved
[0008] The present invention aims to solve the problems of the aforementioned conventional technology by performing the carbonization and activation steps as a one-step process through microwave irradiation of waste paper, thereby improving process economics and efficiency.
[0009] In addition, the present invention aims to recycle waste paper by synthesizing a porous carbon body using waste paper, and to synthesize a porous carbon body that is environmentally friendly and exhibits excellent physical properties. means of solving the problem
[0010] To achieve the aforementioned technical objectives, the present invention discloses a method for manufacturing a porous carbon body derived from waste paper, comprising the steps of: crushing waste paper to form pulp; precipitating the pulp and a basic substance in distilled water to form a pulp mixture; drying the precipitated pulp mixture; introducing an inner container containing the dried pulp mixture into an outer container; and irradiating the inner container and the outer container with microwaves in a sealed space; wherein the inner container and the outer container each have a portion of their upper surface or side surface open independently, and a carbon-based material is included in a mutually isolated portion between the outer surface of the inner container and the inner surface of the outer container.
[0011] Here, the pulp and the basic material may be mixed in a weight ratio of 0.5:1 to 1:10.
[0012] Here, the drying can be performed at 50 to 120 ℃ for 3 to 9 hours.
[0013] Here, the step of irradiating the inner container and the outer container with microwaves in the sealed space can be performed at a power of 500 to 1000 W.
[0014] Here, the step of irradiating the inner container and the outer container with microwaves in the sealed space can be performed in a frequency range of 1.5 to 3.5 GHz.
[0015] Here, the step of irradiating the inner container and the outer container with microwaves in the sealed space can be performed for 15 to 45 minutes.
[0016] Meanwhile, in order to achieve the aforementioned technical objectives, the present invention further discloses a waste paper-derived porous carbon body manufactured according to the above-described method for manufacturing a waste paper-derived porous carbon body.
[0017] Here, the specific surface area of the waste paper-derived porous carbon body is 150 to 350 m² 2 g -1 It could be.
[0018] Here, the total pore volume of the waste paper-derived porous carbon body is 0.1 to 0.25 cm³ 3 g -1 It is possible.
[0019] Here, the carbon element content of the above-mentioned waste-derived porous carbon body may be 75 to 90 at%. Effects of the invention
[0020] The disclosed technology may have the following effects. However, this does not mean that a specific embodiment must include all of the following effects or only the following effects; therefore, the scope of the rights of the disclosed technology should not be understood as being limited by this.
[0021] According to the present invention, by irradiating waste paper with microwaves, the carbonization and activation steps can be performed as a one-step process, thereby improving process economics and efficiency.
[0022] In addition, according to the present invention, by synthesizing a porous carbon body using waste paper, waste paper can be recycled, and a porous carbon body exhibiting excellent physical properties while being environmentally friendly can be synthesized. Brief explanation of the drawing
[0023] FIG. 1 is a flowchart illustrating a method for manufacturing a porous carbon body derived from waste paper according to one embodiment of the present invention. FIG. 2 is a schematic diagram illustrating a method for manufacturing a porous carbon body derived from waste paper according to one embodiment of the present invention. FIG. 3 is an image illustrating the shape of a waste paper-derived porous carbon body according to one embodiment of the present invention. FIG. 4 is an isotherm of N2 adsorption-desorption of a waste paper-derived porous carbon body according to one embodiment of the present invention. Figure 5 is a graph showing the XRD pattern of a waste paper-derived porous carbon body according to one embodiment of the present invention. Figure 6 is a graph showing the results of a Raman spectrum analysis of a waste paper-derived porous carbon body according to one embodiment of the present invention. FIG. 7 is a graph showing the results of a high-resolution spectral analysis of C1s of a waste paper-derived porous carbon body according to one embodiment of the present invention. Figure 8 is the result of an electrochemical performance evaluation according to microwave irradiation time of a waste paper-derived porous carbon body according to one embodiment of the present invention. FIG. 9 shows various scan rates (5 to 200 mV·s) of a waste paper-derived porous carbon body according to one embodiment of the present invention. -1 It is the CV curve at ). FIG. 10 shows various current densities (0.5 to 10 A·g) of a waste paper-derived porous carbon body according to one embodiment of the present invention. -1 This is the GCD curve at ). Figure 11 is a graph showing the results of a comparison of electrochemical performance by type of waste paper for a porous carbon body derived from waste paper according to one embodiment of the present invention. FIG. 12 is a graph showing the results of a comparison of electrochemical performance of a waste paper-derived porous carbon body according to one embodiment of the present invention, by waste paper type and carbonization method. FIG. 13 is an optical image of a methylene blue (MB) solution taken before and after dye adsorption according to the initial input amount of a waste paper-derived porous carbon body according to one embodiment of the present invention. FIG. 14 is a graph showing the results of evaluating the dye removal and adsorption performance of a waste paper-derived porous carbon body according to an embodiment of the present invention, according to the initial input amount and methylene blue (MB) concentration. FIG. 15 is a graph showing the results of dye adsorption kinetics analysis by a pseudo-first-order kinetic model and a pseudo-second-order kinetic model of a waste paper-derived porous carbon body according to one embodiment of the present invention. FIG. 16 is a dye adsorption isotherm analyzed by the Langmuir model and the Freundlich model of a waste paper-derived porous carbon body according to one embodiment of the present invention. FIG. 17 is a schematic diagram illustrating the chemical structures of dyes used to evaluate the dye adsorption performance of a waste paper-derived porous carbon body according to one embodiment of the present invention. FIG. 18 is a graph showing the results of evaluating the dye removal and adsorption performance of various dyes on a waste paper-derived porous carbon body according to one embodiment of the present invention. Specific details for implementing the invention
[0024] The present invention is capable of various modifications and may have various embodiments, and specific embodiments are illustrated in the drawings and described in detail in the detailed description. However, this is not intended to limit the invention to specific embodiments, and it should be understood that the invention includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the invention.
[0025] Similar reference numerals are used for similar components when describing each drawing. Terms such as "first," "second," etc., may be used to describe various components, but said components should not be limited by said terms. These terms are used solely for the purpose of distinguishing one component from another.
[0026] For example, without departing from the scope of the present invention, the first component may be named the second component, and similarly, the second component may be named the first component. The term "and / or" includes a combination of a plurality of related described items or any of a plurality of related described items.
[0027] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which this invention pertains.
[0028] Terms such as those defined in commonly used dictionaries should be interpreted as having meanings consistent with their meanings in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this application.
[0029] Throughout this specification, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.
[0030] As used herein, terms of degree such as “about,” “substantially,” etc., are used to mean at or near the stated value when inherent manufacturing and material tolerances are presented in the stated meaning, and are used to prevent unscrupulous infringers from unfairly exploiting the disclosure in which precise or absolute values are mentioned to aid in understanding the invention. Furthermore, throughout this specification, “a step of” or “a step of” does not mean “a step for”.
[0031] Throughout this specification, the term “combination thereof” included in the Markush-type expression means one or more mixtures or combinations selected from the group consisting of the components described in the Markush-type expression, and means including one or more selected from the group consisting of said components.
[0033] Method for manufacturing a porous carbon body derived from waste paper
[0034] The present specification discloses a method for manufacturing a porous carbon body derived from waste paper, comprising the steps of: crushing waste paper to form pulp; precipitating the pulp and a basic substance in distilled water to form a pulp mixture; drying the precipitated pulp mixture; introducing an inner container containing the dried pulp mixture into an outer container; and irradiating the inner container and the outer container with microwaves in a sealed space; wherein the inner container and the outer container each have a portion of their upper surface or side surface open independently, and a carbon-based material is included in a portion isolated from each other between the outer surface of the inner container and the inner surface of the outer container.
[0035] FIG. 1 is a flowchart illustrating a method for manufacturing a porous carbon body derived from waste paper according to one embodiment of the present invention.
[0036] Referring to FIG. 1, a method for manufacturing a porous carbon body derived from waste paper according to one embodiment of the present invention comprises the steps of: crushing waste paper to form pulp; precipitating the pulp and a basic substance in distilled water to form a pulp mixture; drying the precipitated pulp mixture; introducing an inner container containing the dried pulp mixture into an outer container; and irradiating the inner container and the outer container with microwaves in a sealed space; wherein the inner container and the outer container each have a portion of their upper surface or side surface open independently, and a carbon-based material is contained in a portion isolated from each other between the outer surface of the inner container and the inner surface of the outer container.
[0037] FIG. 2 is a schematic diagram illustrating a method for manufacturing a porous carbon body derived from waste paper according to one embodiment of the present invention.
[0038] Specifically, FIG. 2a is a schematic diagram illustrating the synthesis process of a waste paper-derived porous carbon body according to one embodiment of the present invention, and FIG. 2b is a cross-sectional view illustrating the arrangement structure of synthesis containers for a waste paper-derived porous carbon body according to one embodiment of the present invention.
[0039] Referring to FIG. 2a, it can be seen that a porous carbon body derived from waste paper according to one embodiment of the present invention performs carbonization and activation processes in one step by short-duration microwave irradiation without performing them separately.
[0040] Additionally, referring to FIG. 2b, it can be seen that a porous carbon body derived from waste paper according to one embodiment of the present invention is carbonized and activated by introducing an inner container containing the dried pulp mixture into an outer container and irradiating the inner container and the outer container with microwaves in a sealed space.
[0041] The method for manufacturing a porous carbon body according to the present invention utilizes waste paper, which is generated in large quantities from households and companies among various biomass, as a raw material. This resolves environmental pollution caused by waste paper, increases the potential for utilizing waste paper, and further enables the use of waste paper as an adsorption material and an electrode material for energy storage devices.
[0042] The above waste paper may include one or more waste papers selected from the group consisting of old corrugated cardboard (OCC), white ledgar (WL), old magazine (OMG), and old newspaper (ONP), but is not limited thereto.
[0043] Due to differences in the composition and characteristics of cellulose fibers resulting from processing and chemical treatment depending on the type of waste paper, differences in physical properties and electrical performance may occur when the above-mentioned porous carbon body is synthesized.
[0044] The above waste paper may be newspaper. When the above waste paper is newspaper, the physical properties and electrical performance of the synthesized porous carbon body may be further improved.
[0045] The step of forming a pulp mixture by precipitating the above pulp and basic material in distilled water may be a step of treating the pulp with a base to cause delignification in which lignin is removed. Cellulosic biomass such as waste paper contains lignin, hemicellulose, and cellulose, and the above base treatment may remove lignin and hemicellulose from the waste paper pulp and soften the waste paper pulp.
[0046] The above basic substance may include one or more basic substances selected from alkali metal hydroxides and alkaline earth metal hydroxides, but is not limited thereto.
[0047] It is preferable that the pulp and the basic material be mixed in a weight ratio of 0.5:1 to 1:10, more preferable that the pulp and the basic material be mixed in a weight ratio of 0.5 to 1:5, and most preferable that the pulp and the basic material be mixed in a weight ratio of 1:1. For example, if the pulp and the basic material are mixed in a weight ratio of less than 0.5:1, the amount of porous carbon body synthesized with the pulp is smaller than the amount of the basic material being processed, which may result in a problem of reduced process efficiency. Conversely, if the pulp and the basic material are mixed in a weight ratio exceeding 1:10, the amount of the basic material being processed increases, which may result in reduced process efficiency and a problem where the physical properties of the pulp are altered in a manner different from what is intended. When mixed in a weight ratio of 0.5 to 1:5, or further in a weight ratio of 1:1, the pulp can be efficiently softened without loss of time and economic costs due to the use of small or excessive materials and base treatment.
[0048] Since there is a limit to the amount of basic solution that the pulp can absorb, the pulp and the basic material can exhibit the effect of maximizing process efficiency while ensuring the best carbonization synthesis when mixed in a weight ratio of 1:1. When the pulp and the basic material are mixed in a weight ratio of 1:1 to 1:5, there may not be a significant difference between the carbonization synthesis yield at a mixing ratio of 1:1 and the carbonization synthesis yield at a mixing ratio higher than that.
[0049] The above drying is preferably performed at 50 to 120°C for 3 to 9 hours, more preferably at 70 to 100°C for 3 to 9 hours, and most preferably at 70 to 100°C for 5 to 7 hours. For example, if the drying is performed under conditions of 50°C and less than 3 hours, the precipitated pulp mixture may not be completely dried, which may result in a problem where it is not sufficiently carbonized and activated in the subsequent microwave irradiation step. Conversely, if the drying is performed under conditions of 120°C and more than 9 hours, the process time may be prolonged, and the problem of increased energy consumption due to excessive heat treatment prior to microwave irradiation may occur.
[0050] The step of introducing an inner container containing the dried pulp mixture into an outer container may further enhance the heat absorption rate of the dried pulp mixture through the microwave absorption, heat conversion, and heat transfer capabilities of the carbon-based material present in the mutually isolated portion between the outer surface of the inner container and the inner surface of the outer container when the dried pulp mixture is irradiated with microwaves, while also improving the purity of the porous carbon body synthesized by separating the dried pulp mixture and the carbon-based material through the inner container.
[0051] The above carbon-based material may include one or more selected from the group consisting of artificial graphite, natural graphite, and hard carbon, but is not limited thereto.
[0052] Unlike biomass such as waste paper, which has a low microwave absorption rate before carbonization, the above-mentioned carbon-based material rapidly absorbs microwaves and converts them into heat, and can perform the role of transferring the converted heat to biomass such as waste paper. Through this, the above-mentioned carbon-based material can transfer the converted heat to the above-mentioned dried pulp mixture, thereby enabling the carbonization and activation of the waste paper.
[0053] The carbon-based material is separated from the dried pulp mixture by the inner container, thereby transferring heat without mixing with the dried pulp mixture, so that the carbon-based material does not exist as an impurity in the porous carbon body after synthesis, and accordingly, the purity of the porous carbon body is improved, and thus physical and electrical properties can be improved.
[0054] The step of irradiating the inner container and the outer container with microwaves in the above-mentioned sealed space is a step of carbonizing and activating the pulp mixture. The microwave-induced carbonization process of the present invention can reduce energy consumption and simplify the process by carrying out carbonization and activation together by irradiating microwaves in a sealed space without performing carbonization and activation in separate steps.
[0055] In the microwave-induced carbonization process of the present invention, since the dried pulp mixture and graphite, which is a heat conversion and heat transfer material, are irradiated together with microwaves within a sealed space, carbon dioxide generated from the dried pulp mixture and graphite through microwave irradiation fills the inside of the sealed space, thereby creating an inert gaseous state inside the sealed space, so that carbonization and activation can be performed as a one-step process.
[0056] The step of irradiating the inner container and the outer container with microwaves in the sealed space is preferably performed at a power of 500 to 1000 W, the step of irradiating the inner container and the outer container with microwaves in the sealed space is more preferably performed at a power of 600 to 900 W, and the step of irradiating the inner container and the outer container with microwaves in the sealed space is most preferably performed at a power of 700 to 800 W.
[0057] The step of irradiating the inner container and the outer container with microwaves in the above-mentioned sealed space is preferably performed in a frequency range of 1.5 to 3.5 GHz, and the step of irradiating the inner container and the outer container with microwaves in the above-mentioned sealed space is more preferably performed in a frequency range of 2 to 3 GHz.
[0058] The step of irradiating the inner container and the outer container with microwaves in the sealed space is preferably performed for 15 to 45 minutes, more preferably for 20 to 40 minutes, and most preferably for 25 to 35 minutes.
[0059] For example, if the step of irradiating the inner container and the outer container with microwaves in a sealed space is performed under conditions of 500 W power, 1.5 GHz frequency, and less than 15 minutes, the carbonization and activation of the dried pulp mixture may not occur sufficiently, resulting in a decrease in the synthesis rate of the porous carbon body and a deterioration in the physical properties and electrochemical performance of the porous carbon body. Conversely, if the step of irradiating the inner container and the outer container with microwaves in a sealed space is performed under conditions of 1000 W power, 3.5 GHz frequency, and more than 45 minutes, the physical properties of the porous carbon body may change due to excessive microwave irradiation, or problems may arise in which energy consumption and costs increase during the process, leading to a decrease in efficiency.
[0060] The power and frequency conditions of the microwave irradiation described above are typical output conditions of a household microwave oven, and the waste paper-derived porous carbon body of the present invention can be manufactured in a short time using a household microwave oven.
[0061] The method may further include the step of washing the microwave-irradiated pulp mixture with an acidic solution and distilled water until it becomes neutral after the step of irradiating the inner container and the outer container with microwaves in the sealed space; and the step of drying the pulp mixture from which impurities have been removed by heat treatment at 90 to 120°C for 4 to 8 hours.
[0063] Porous carbon material derived from waste paper
[0064] Meanwhile, the present specification further discloses a waste paper-derived porous carbon body manufactured according to the method for manufacturing a waste paper-derived porous carbon body described above.
[0065] The specific surface area of the above-mentioned waste-derived porous carbon body is 150 to 350 m² 2 g -1It is preferable that the specific surface area of the above-mentioned waste paper-derived porous carbon body is 200 to 350 m² 2 g -1 It is more preferable that the specific surface area of the above-mentioned waste paper-derived porous carbon body is 250 to 350 m² 2 g -1 It is most desirable that the specific surface area of the above-mentioned waste paper-derived porous carbon body is 150 m² 2 g -1 If it is less than, a problem may arise in which the physical properties, adsorption performance, and electrochemical performance of the porous carbon body deteriorate due to the low specific surface area. The waste paper-derived porous carbon body is 150 to 350 m 2 g -1 It represents a specific surface area within a range, and as the specific surface area increases within the range, the physical properties, adsorption performance, and electrochemical performance of the porous carbon body can be improved.
[0066] The total pore volume of the above waste-derived porous carbon body is 0.1 to 0.25 cm³ 3 g -1 It is preferable that the total pore volume of the waste paper-derived porous carbon body is 0.15 to 0.25 cm³ 3 g -1 It is desirable that the total pore volume of the above waste paper-derived porous carbon body is 0.1 cm. 3 g -1 If it is less than, a problem may arise in which the physical properties, adsorption performance, and electrochemical performance of the porous carbon body deteriorate due to the low total pore volume. The waste paper-derived porous carbon body is 0.1 to 0.25 cm 3 g -1 It represents the total pore volume of the range, and as the total pore volume increases within the above range, the physical properties, adsorption performance, and electrochemical performance of the porous carbon body can be improved.
[0067] The above-mentioned waste paper-derived porous carbon material may include both micropores and mesopores. By including a variety of pores formed in micro and meso sizes, the above-mentioned waste paper-derived porous carbon material can adsorb substances of various sizes, and accordingly, adsorption performance and pollutant purification performance can be improved.
[0068] The micropore volume of the above-mentioned waste paper-derived porous carbon body is 0.05 to 0.15 cm³ 3 g -1 It may be, but is not limited to this.
[0069] The mesopore volume of the above waste paper-derived porous carbon body is 0.05 to 0.15 cm³ 3 g -1 It may be, but is not limited to this.
[0070] It is preferable that the carbon element content of the above-derived porous carbon body is 75 to 90 at%, and it is more preferable that the carbon element content of the above-derived porous carbon body is 80 to 90 at%. For example, if the carbon element content of the above-derived porous carbon body is less than 75 at%, carbonization may not proceed sufficiently to the desired extent, and problems may arise in which the physical properties, adsorption performance, and electrochemical performance of the above-derived porous carbon body are degraded. Conversely, if the carbon element content of the above-derived porous carbon body is 90 at% or more, excessive carbonization may be performed, and consequently, problems may arise in which the physical properties, adsorption performance, and electrochemical performance of the above-derived porous carbon body are degraded.
[0071] The above porous carbon body can exhibit excellent physical properties, adsorption performance, and electrochemical performance by being synthesized by the microwave-induced carbonization process of the present invention.
[0072] The charge transfer resistance of the porous carbon body may be 50 to 65 Ω. The porous carbon body may exhibit excellent electrochemical properties by exhibiting a low charge transfer resistance within the aforementioned range.
[0073] The above porous carbon body can promote efficient charge transfer and improved electrochemical performance by exhibiting a high degree of graphitization (graphitivity) through the microwave-induced carbonization process of the present invention, thereby improving electrical conductivity and reducing electrical resistance.
[0074] The porous carbon body of the present invention is an excellent supercapacitor electrode material exhibiting EDLC characteristics, and can be applied to the electrodes of supercapacitors and utilized in various other energy storage fields.
[0075] In addition, since the present invention exhibits excellent removal and adsorption performance for various pollutants, it can be applied to various pollution purification technologies.
[0077] Hereinafter, the claims of this specification will be explained in more detail with reference to the attached drawings and embodiments. However, as the drawings and embodiments presented in this specification may be modified in various ways by a person skilled in the art and may take various forms, the details described in this specification should not be interpreted as limiting the invention to a specific disclosed form, but rather as including all equivalents and substitutions that fall within the spirit and scope of the invention. Furthermore, the attached drawings are presented to help a person skilled in the art understand the invention more accurately and may be depicted in an exaggerated or reduced size compared to the actual size.
[0079] {Examples and Evaluation}
[0080] <Example>
[0081] Example 1
[0082] 1. Manufacture of porous carbon materials derived from waste paper
[0083] Newspaper (NP) was cut into small pieces and then ground into fine microfiber fibers using a grinder. The paper fibers obtained in this way were immersed in a potassium hydroxide (KOH, 95%, Samjeon Sunyak) solution. Subsequently, the paper fibers and potassium hydroxide were mixed in distilled water at a weight ratio of 1:1 and immersed for 12 hours. Afterward, the paper fibers were collected and completely dried in an oven at 80°C for 6 hours. Then, 2.0 g of the dried paper fibers were transferred to a beaker, placed in an alumina crucible filled with graphite (Samjeon Sunyak), and microwaved for 30 minutes using a microwave oven (Samsung, 700 W, 2.45 GHz). The waste paper-derived porous carbon body synthesized through microwave irradiation (hereinafter referred to as the “porous carbon body”) was washed with hydrochloric acid (HCl, Daejeong Hwakum) and distilled water until neutral to remove impurities. The porous carbon material from which impurities had been removed was dried in an oven at 105°C for 6 hours and finely ground to produce a newspaper-derived porous carbon material (NPC).
[0084] 2. Fabrication of supercapacitor electrodes containing waste paper-derived porous carbon materials
[0085] To evaluate the electrochemical performance of the porous carbon body of the present invention, a supercapacitor electrode was prepared by drop casting using the waste paper-derived porous carbon body ink of the present invention. An ink was prepared by suspending 5 mg of waste paper-derived porous carbon body in a mixed solution of Nafion 117 solution and 1000 μL of isopropyl alcohol mixed in a volume ratio of 1:9, and the solution was treated in a water bath ultrasonic device for 30 minutes. 60 μL of the dispersed ink was placed on carbon paper (1 cm 2 A supercapacitor electrode was prepared by dropping it into ) and drying it at room temperature. (Hereinafter, the newspaper-derived porous carbon (NPC) and the supercapacitor electrode containing it are referred to as “Example 1”).
[0087] Example 2
[0088] A porous carbon material derived from box paper (BPC) and a supercapacitor electrode containing the same were prepared in the same manner as in Example 1, except that box paper (BP) was used instead of newspaper (hereinafter referred to as “Example 2”).
[0090] Comparative Example 1
[0091] It is a newspaper (Newspaper, NP) that has not undergone a microwave-induced carbonization process (hereinafter referred to as “Comparative Example 1”).
[0093] Comparative Example 2
[0094] It is a box paper (BP) that has not undergone a microwave-induced carbonization process (hereinafter referred to as “Comparative Example 2”).
[0096] Comparative Example 3
[0097] Newspaper (NP) was immersed in potassium hydroxide (KOH, 95%, Samjin Chemical) and dried, and then subjected to 10 ℃·min in a horizontal flow furnace (Pyrotec). -1 Pure N2 gas (50 mL·min) at a rate of temperature rise -1 A newspaper-derived porous carbon body (PNP) based on a pyrolysis carbonization process and a supercapacitor electrode containing the same were prepared by carbonizing at 800°C for 30 minutes under the flow of ) (hereinafter referred to as “Comparative Example 3”).
[0099] <Evaluation>
[0100] 1. Evaluation of the Synthesis of Porous Carbon Materials
[0101] FIG. 3 is an image illustrating the shape of a waste paper-derived porous carbon body according to one embodiment of the present invention.
[0102] Specifically, FIG. 3 illustrates photographic images, optical images, and SEM images of Example 1, Example 2, Comparative Example 1, and Comparative Example 2, respectively, where FIG. 3a to 3c are images of Comparative Example 1, FIG. 3d to 3f are images of Example 1, FIG. 3g to 3i are images of Comparative Example 2, and FIG. 3j to 3l are images of Example 2.
[0103] Referring to Fig. 3, the morphological structures of different types of waste paper before and after carbonization can be observed. Before undergoing the microwave-induced carbonization process, Comparative Examples 1 and 2 exhibited a fibrous structure of approximately 5 μm, and no pores were observed. After carbonization, Examples 1 and 2 turned black and their texture became powdery, and the interconnected porous structure identified in Comparative Example 3, which underwent pyrolysis, was observed identically on the surfaces of Examples 1 and 2. The appearance of this black powder and interconnected porous structure indicates that both carbonization and activation were successfully performed through the microwave-induced carbonization process of the present invention.
[0104] In addition, when newspaper was used as a raw material and synthesized under different conditions during the microwave-induced carbonization process of the present invention, with microwave irradiation times of 10 minutes, 20 minutes, 30 minutes, and times exceeding 30 minutes, it was confirmed that carbonization synthesis did not occur to the extent that it could be visually confirmed at times of 10 minutes or less, that in the time range of 20 minutes to 30 minutes, the degree of carbonization increased as the irradiation time increased, and that the carbonization yield decreased when microwaves were irradiated for a time exceeding 30 minutes. Accordingly, it was confirmed that the physical properties and electrochemical performance of the porous carbon body are optimized when microwaves are irradiated for 25 to 35 minutes in the microwave-induced carbonization process of the present invention at a power of 700 to 800 W and a frequency range of 2 to 3 GHz.
[0105] FIG. 4 is an isotherm of N2 adsorption-desorption of a waste paper-derived porous carbon body according to one embodiment of the present invention.
[0106] Table 1 shows the results of the surface characteristic analysis of Example 1, Example 2, and Comparative Example 3.
[0107] Referring to FIG. 4, the surface and pore characteristics of Example 1 and Example 2 can be confirmed based on the N2 adsorption-desorption measurement results. As a result of the N2 adsorption-desorption measurement, the specific surface area of Example 1 and Example 2 is 281 m², respectively. 2 ·g -1 and 193 m 2 ·g -1 It can be confirmed that... According to Figure 4, among the pores of Example 1 and Example 2, the type with more micropores is... and it can be seen that there are abundant micropores and mesopores. In particular, Example 1 was found to have a larger specific surface area, total pore volume, micropore volume, and mesopore volume than Example 2. Detailed figures for specific surface area and pore volume can be confirmed through Table 1 below.
[0108] division Specific surface area (m²) 2 ·g -1 ) Total pore volume (cm²) 3 ·g -1 ) Micropore volume (cm²) 3 ·g -1 ) Mesopore volume (cm²) 3 ·g -1 ) Micro-porosity (%) NPC 281 0.197 0.100 0.097 50.8 BPC 193 0.140 0.0735 0.0665 52.5 PNP 725 0.431 0.239 0.192 55.5
[0109] Figure 5 is a graph showing the XRD pattern of a waste paper-derived porous carbon body according to one embodiment of the present invention.
[0110] Specifically, FIG. 5a is the XRD pattern of Example 1 and Comparative Example 1, and FIG. 5b is the XRD pattern of Example 2 and Comparative Example 2.
[0111] Referring to FIG. 5, the XRD patterns of Example 1, Comparative Example 1, Example 2, and Comparative Example 2 can be observed. Before undergoing the microwave-induced carbonization process, Comparative Example 1 and Comparative Example 2 exhibited diffraction peaks at 2θ of 22.5° and 16.4°, respectively, corresponding to the (002) and (110) planes of the cellulose structure. In the case of Example 1 and Example 2, after the microwave-induced carbonization process, the (110) diffraction peak disappeared and the (002) peak weakened and broadened, which means that the raw materials, Comparative Example 1 and Comparative Example 2, changed from a cellulose structure to a carbonaceous structure. In addition, a peak appeared near 2θ = 42.0°, which corresponds to the graphite (100) plane, and the diffraction peaks observed at 29.5°, 36.0°, 39.5°, 43.3°, 47.7°, 48.6° and 57.6° were identified as belonging to calcite (JCPDS 5-0586), which is used to increase brightness, softness and opacity in paper manufacturing.
[0112] Figure 6 is a graph showing the results of a Raman spectrum analysis of a waste paper-derived porous carbon body according to one embodiment of the present invention.
[0113] Referring to FIG. 6, the results of the Raman spectrum analysis performed for the further structural characterization of Examples 1 and 2 can be seen. The Raman spectrum shows two characteristic peaks of the intrinsic carbon material, namely the D band (~1340 cm⁻¹) indicating a disordered structure. -1 ) and mainly sp 2 G band (~1600 cm⁻¹) representing a graphite structure dominated by bonding -1 ...represented. The disordered structural characteristics of the defective Examples 1 and 2 were confirmed through the presence of a broad D band. The intensity ratio between the D band and the G band in Raman spectroscopy (I D / I GThe strength ratio measures the degree of graphitization of carbon materials, and a higher strength ratio indicates a disordered structure, while a lower strength ratio indicates a higher degree of graphitization. The strength ratios of Example 1, Example 2, and Comparative Example 3 are 0.86, 0.99, and 0.96, respectively. When comparing the strength ratios of the three porous carbon bodies, it can be confirmed that Example 1 exhibits a more distinct graphite structure than the other two.
[0114] FIG. 7 is a graph showing the results of a high-resolution spectral analysis of C1s of a waste paper-derived porous carbon body according to one embodiment of the present invention.
[0115] Specifically, FIG. 7a is the result of the high-resolution spectrum analysis of C1s in Example 1, and FIG. 7b is the result of the high-resolution spectrum analysis of C1s in Example 2.
[0116] Table 2 shows the XPS analysis results of Example 1, Example 2, and Comparative Examples 1 to 3.
[0117] Referring to Figure 7 and Table 2, the results of elemental content measurement via XPS analysis of the embodiments and comparative examples of the present invention, as well as the results of C1s high-resolution spectrum analysis of Examples 1 and 2, can be confirmed. As indicated in Table 2, the relative content of C increased in all porous carbon bodies after carbonization and activation, while the content of O and N decreased. The C1s spectra of Examples 1 and 2 were decomposed into four peaks due to CC (284.6 eV), CO (285.6 eV), C=O (286.6 eV), and OCO (288.6 eV), respectively. After the synthesis process, the relative proportion of oxygen groups such as CO, C=O, and OCO decreased significantly, while the proportion of CC bonds in the graphite structure increased. These results are consistent with the Raman spectrum analysis results in Figure 6, which show the presence of the graphite structure, confirming that the carbonization of the waste paper-derived porous carbon body of the present invention was successfully achieved.
[0118] division C (%) O (%) N (%) NP 67.5 32.1 0.3 NPC 84.4 15.6 <0.1 BP 71.7 26.7 1.6 BPC 77.4 22.2 0.4 PNP 71.5 26.3 2.2
[0120] 2. Electrochemical Performance Evaluation of Porous Carbon Materials
[0121] Figure 8 is the result of an electrochemical performance evaluation according to microwave irradiation time of a waste paper-derived porous carbon body according to one embodiment of the present invention.
[0122] Specifically, FIG. 8a shows 1 A·g of a newspaper-derived porous carbon material according to microwave irradiation time. -1 Figure 8b is the GCD curve at a current density, and Figure 8b shows various current densities (0.5 to 10 A·g) of a newspaper-derived porous carbon body according to microwave irradiation time. -1 This is the result of the cost measurement in ).
[0123] Referring to Fig. 8a, when the microwave irradiation time was varied to 10, 20, and 30 minutes, it can be confirmed that the newspaper-derived porous carbon material treated for 30 minutes was most successfully carbonized and synthesized, exhibiting the best electrochemical performance by displaying a clear triangular shape with a large region in the GCD curve compared to the treatments of 10 and 20 minutes. Specifically, 1 A·g -1 The discharge time was longest at the current density, showing high energy storage capacity. Additionally, referring to Fig. 8b, when the specific capacity was calculated from Fig. 8a, the specific capacity of the newspaper-derived porous carbon material treated for 30 minutes was the highest, and similar to Fig. 8a, it can be confirmed that the electrochemical performance of the porous carbon material is best at a treatment time of 30 minutes.
[0124] FIG. 9 shows various scan rates (5 to 200 mV·s) of a waste paper-derived porous carbon body according to one embodiment of the present invention. -1 It is the CV curve at ).
[0125] Specifically, FIG. 9a is the CV curve of Example 1, and FIG. 9b is the CV curve of Example 2.
[0126] Referring to FIG. 9, various scan rates (5 to 200 mV·s) of Example 1 and Example 2 -1 It can be confirmed that the CV curves measured in ) all exhibit a rectangular shape, indicating electric double layer capacitor (EDLC) characteristics. This indicates EDLC characteristics that are affected by pseudocapacitance due to the high oxygen functional group content. These results indicate that the waste paper-derived porous carbon material of the present invention has potential for use as an electrode material for supercapacitors.
[0127] FIG. 10 shows various current densities (0.5 to 10 A·g) of a waste paper-derived porous carbon body according to one embodiment of the present invention. -1 This is the GCD curve at ).
[0128] Specifically, FIG. 10a is the GCD curve of Example 1, and FIG. 10b is the GCD curve of Example 2.
[0129] Referring to FIG. 10, various current densities (0.5 to 10 A·g) of Examples 1 and 2 -1 It can be confirmed that the GCD curves measured in ) all exhibit a triangular shape, indicating electric double layer capacitor (EDLC) characteristics. This is consistent with the results of the CV curve in Fig. 9.
[0130] Figure 11 is a graph showing the results of a comparison of electrochemical performance by type of waste paper for a porous carbon body derived from waste paper according to one embodiment of the present invention.
[0131] Specifically, FIG. 11a is 100 mV·s -1 This is the CV curve at a scan rate of , and Fig. 11b is for 0.5 A·g -1 This is the GCD curve at the current density.
[0132] Referring to Fig. 11, the results of the comparison of electrochemical characteristics of Example 1 and Example 2 can be seen. When comparing the CV curves and GCD curves of Example 1 and Example 2, it can be seen that Example 1 exhibits a larger CV curve and a GCD curve with a longer discharge time. The larger area formed by the rectangle of the CV curve indicates higher capacitance, which corresponds to the longer discharge time of the GCD curve.
[0133] FIG. 12 is a graph showing the results of a comparison of electrochemical performance of a waste paper-derived porous carbon body according to one embodiment of the present invention, by waste paper type and carbonization method.
[0134] Specifically, FIG. 12a shows various current densities (0.5 to 10 A·g -1 This is the EIS analysis result at ), and Fig. 12b is for various current densities (0.5 to 10 A·g -1 This is the result of the cost measurement in ).
[0135] Referring to FIG. 12, the superior electrochemical performance of Example 1 compared with Comparative Example 3 can be confirmed.
[0136] Referring to FIG. 12a, it can be seen that the Nyquist plot of Comparative Example 3 shows a much larger semicircle compared to Examples 1 and 2, indicating a higher equivalent series resistance (charge transfer resistance, ESR). The Nyquist plot of the waste paper-derived porous carbon body of the present invention showed a semicircle and a 45° slope line. In terms of equivalent series resistance, Examples 1 and 2 recorded values of 60 Ω and 54 Ω, respectively, while Comparative Example 3 recorded a value of approximately 306 Ω.
[0137] Referring to Fig. 12b, 0.5 A·g -1 The specific capacities of Example 1, Example 2, and Comparative Example 3 calculated from the GCD discharge curves at the current density can be confirmed. Example 1 and Example 2 are 237.7 F·g, respectively. -1 and 133.0 F·g-1 The specific capacity value was shown. Example 1 exhibits a higher specific capacity at various current densities, and at a high current density (10 A·g -1 128.9 F·g even under the condition of ) -1 It can be confirmed that it exhibits superior rate performance compared to Example 2, exhibiting a specific capacity. Although Example 1 has a higher equivalent series resistance value than Example 2, it demonstrates superior electrochemical performance. These results are attributed to the high ion transport capacity, expanded ion-accessible surface area, and increased pore volume, which promote rapid ion transport and diffusion across the entire surface area. Furthermore, as observed in the Raman spectrum, the high degree of graphitization in Example 1 leads to improved electrical conductivity and reduced electrical resistance, thereby facilitating efficient charge transfer and enhanced electrochemical performance. These characteristics contribute to improving the overall electrochemical performance of Example 2.
[0138] The specific capacity of Comparative Example 3 is 2 A·g -1 38.9 F·g at a current density -1 177.6 F·g, which is the specific amount of Example 1 -1 It can be confirmed that it is lower. Comparative Example 3 had a higher specific surface area than Examples 1 and 2, but its specific capacity was lower than that of Example 1. This is because Comparative Example 3 contains an excessive amount of oxygen-containing functional groups, which disrupts the pore structure and increases resistance to ion permeation, thereby inducing a degradation of performance. Furthermore, as analyzed by the Raman spectrum, the degree of graphitization in Comparative Example 3 is lower than that of Example 1, and it was found that as the degree of graphitization decreases, the ionic resistance increases and the electrical conductivity decreases, resulting in a deterioration of electrochemical performance. Accordingly, it was confirmed that the waste paper-derived porous carbon material produced by the microwave-induced carbonization process of the present invention is an excellent material that is economical due to the simple process and can be utilized as a promising material in electrochemical capacitor applications.
[0140] 3. Evaluation of Dye Adsorption Performance of Porous Carbon Materials
[0141] FIG. 13 is an optical image of a methylene blue (MB) solution taken before and after dye adsorption according to the initial input amount of a waste paper-derived porous carbon body according to one embodiment of the present invention.
[0142] FIG. 14 is a graph showing the results of evaluating the dye removal and adsorption performance of a waste paper-derived porous carbon body according to an embodiment of the present invention, according to the initial input amount and methylene blue (MB) concentration.
[0143] Specifically, FIG. 14a shows the results of the dye removal and adsorption performance evaluation according to the initial input amount of Example 1, and FIG. 14b shows the results of the dye removal and adsorption performance evaluation according to the methylene blue (MB) concentration of Example 2.
[0144] Referring to Figures 13 and 14a, the concentration of methylene blue is 65 mg / L -1 When set to [value], the dye removal efficiency and adsorption capacity according to the initial input amount of Example 1 can be confirmed. To verify the water purification ability of the porous carbon body of the present invention, a dye adsorption performance evaluation was performed. Since one of the key factors improving the dye adsorption ability of carbon materials is surface area, particularly the solubility of the porous structure, Example 1, which has superior surface area and pore volume compared to Example 2, was selected as the adsorbent for the evaluation. The concentration of methylene blue was 65 mg / L -1 When fixed at [value], the dye removal efficiency showed a corresponding increasing trend as the volume of Example 1 increased, reaching 88.2 ± 2% after 1 hour for a volume of 0.15 g. Conversely, the adsorption capacity decreased as the amount of Example 1 increased, which is due to the limited initial amount of methylene blue present. When the methylene blue adsorption performance was measured using 0.15 g of Comparative Example 3 and compared with Example 1, Comparative Example 3 showed a methylene blue removal efficiency of 88.9 ± 1% and 17.1 mg·g -1By achieving the adsorption capacity of Example 1 (88.2 ± 2% and 20.1 mg·g -1 It showed a value similar to that of ). Accordingly, it was confirmed that even when a waste paper-derived porous carbon body is manufactured by the microwave-induced carbonization process of the present invention, which has lower energy consumption and a simpler process compared to pyrolysis, it can exhibit excellent water purification capabilities comparable to those of a waste paper-derived porous carbon body produced by pyrolysis.
[0145] Referring to FIG. 14b, various initial methylene blue (MB) concentrations (15 to 60 mg·L) -1 The results of the dye removal and adsorption performance evaluation of Example 1 according to ) can be confirmed. As the initial concentration of methylene blue increased, the adsorption capacity of Example 1 increased. This may be because the resistance to the adsorption of dye molecules decreases as the dye concentration increases. Consequently, the amount of adsorbed dye molecules increased, and Example 1 showed a dye removal efficiency of over 90% at various methylene blue concentrations and demonstrated excellent dye removal efficiency with a maximum dye removal efficiency of 95.0±1%.
[0146] FIG. 15 is a graph showing the results of dye adsorption kinetics analysis by a pseudo-first-order kinetic model and a pseudo-second-order kinetic model of a waste paper-derived porous carbon body according to one embodiment of the present invention.
[0147] Specifically, FIG. 15a is the result of dye adsorption kinetics analysis using the first-order reaction rate model of Example 1, and FIG. 15b is the result of dye adsorption kinetics analysis using the second-order reaction rate model of Example 1.
[0148] Referring to FIG. 15, the adsorption of methylene blue for Example 1 is based on a first-order reaction kinetics model (R 2 =0.9987) is a second-order reaction rate model (R 2It can be confirmed that it clearly follows a second-order reaction rate model, as the linear correlation is superior to that of =0.9173.
[0149] FIG. 16 is a dye adsorption isotherm analyzed by the Langmuir model and the Freundlich model of a waste paper-derived porous carbon body according to one embodiment of the present invention.
[0150] Specifically, FIG. 16a is the dye adsorption isotherm analyzed by the Langmuir model of Example 1, and FIG. 16b is the dye adsorption isotherm analyzed by the Freundlich model of Example 1.
[0151] Referring to FIG. 16, in the case of Example 1, the Langmuir model (R 2 =0.9705) This Freundlich model (R 2 It matched the result data of Example 1 better than (=0.8326), which confirms that Example 1 exhibited monolayer adsorption characteristics.
[0152] FIG. 17 is a schematic diagram illustrating the chemical structures of dyes used to evaluate the dye adsorption performance of a waste paper-derived porous carbon body according to one embodiment of the present invention.
[0153] Referring to FIG. 17, it can be seen that comprehensive adsorption experiments were performed using various dye solutions, such as methylene blue (MB), rhodamine 6G (R6G), and methyl orange (MO), to demonstrate the water pollutant removal ability of the porous carbon body of the present invention. Here, methylene blue and rhodamine 6G exhibit cationic characteristics, whereas methyl orange exhibits anionic characteristics.
[0154] FIG. 18 is a graph showing the results of evaluating the dye removal and adsorption performance of various dyes on a waste paper-derived porous carbon body according to one embodiment of the present invention.
[0155] Specifically, FIG. 18a is a graph showing the time-dependent dye removal efficiency for various dyes of Example 1, and FIG. 18b is a graph showing the dye removal efficiency and adsorption capacity for various dyes when the initial input amount of Example 1 is fixed at 0.15g.
[0156] Referring to Fig. 18, it can be observed that after 60 minutes of dye adsorption, the dye removal efficiencies of the cationic dyes methylene blue (88.2±2%) and R6G (58.9±4%) are significantly higher than those of the anionic dye methyl orange (42.0±4%). This difference may be due to the intrinsic electronegativity of Example 1 resulting from the oxygen-containing functional groups. These oxygen functional groups are advantageous for van der Waals forces and electrostatic interactions, particularly electrostatic interactions with cationic dyes. Methylene blue is 2.29 nm 2 0.95 nm, which is a relatively small molecular size compared to R6G, which has a molecular size. 2 Because it represents, methylene blue could diffuse more easily through the structure of Example 1 and induce greater adsorption capacity at the binding site.
[0158] According to the present invention, by irradiating waste paper with microwaves, the carbonization and activation steps can be performed as a one-step process, thereby improving process economics and efficiency.
[0159] In addition, according to the present invention, by synthesizing a porous carbon body using waste paper, waste paper can be recycled, and a porous carbon body exhibiting excellent physical properties while being environmentally friendly can be synthesized.
[0160] The foregoing description of the present invention is for illustrative purposes only, and those skilled in the art will understand that other specific forms can be easily modified without altering the technical concept or essential features of the present invention. Therefore, the embodiments described above should be understood as illustrative in all respects and not restrictive. For example, each component described as a single unit may be implemented in a distributed manner, and components described as distributed may likewise be implemented in a combined form.
[0161] The scope of the present invention is defined by the claims set forth below rather than by the detailed description above, and all modifications or variations derived from the meaning and scope of the claims and equivalent concepts thereof should be interpreted as being included within the scope of the present invention.
Claims
Claim 1 A method for manufacturing a porous carbon body derived from waste paper, comprising: a step of crushing waste paper to form pulp; a step of precipitating the pulp and a basic substance in distilled water to form a pulp mixture; a step of drying the precipitated pulp mixture; a step of introducing an inner container containing the dried pulp mixture into an outer container; and a step of irradiating the inner container and the outer container with microwaves in a sealed space; wherein the inner container and the outer container each have a portion of their upper surface or side surface open independently, and a carbon-based material is included in a mutually isolated portion between the outer surface of the inner container and the inner surface of the outer container. Claim 2 A method for manufacturing a porous carbon body derived from waste paper according to claim 1, wherein the pulp and the basic material are mixed in a weight ratio of 0.5:1 to 1:
10. Claim 3 A method for manufacturing a porous carbon body derived from waste paper according to claim 1, wherein the drying is performed at 50 to 120 ℃ for 3 to 9 hours. Claim 4 A method for manufacturing a porous carbon body derived from waste paper, wherein, in claim 1, the step of irradiating the inner container and the outer container with microwaves in the sealed space is performed at a power of 500 to 1000 W. Claim 5 A method for manufacturing a porous carbon body derived from waste paper according to claim 1, wherein the step of irradiating the inner container and the outer container with microwaves in the sealed space is performed in a frequency range of 1.5 to 3.5 GHz. Claim 6 A method for manufacturing a porous carbon body derived from waste paper according to claim 1, wherein the step of irradiating the inner container and the outer container with microwaves in the sealed space is performed for 15 to 45 minutes. Claim 7 A porous carbon body derived from waste paper manufactured according to the manufacturing method of any one of paragraphs 1 to 6. Claim 8 In claim 7, the specific surface area of the waste paper-derived porous carbon body is 150 to 350 m² 2 g -1 Phosphorus, waste-derived porous carbon material. Claim 9 In claim 7, the total pore volume of the waste paper-derived porous carbon body is 0.1 to 0.25 cm³ 3 g -1 Phosphorus, waste-derived porous carbon material. Claim 10 In claim 7, the waste paper-derived porous carbon body has a carbon element content of 75 to 90 at% with respect to the waste paper-derived porous carbon body.
Citation Information
Patent Citations
Method for prepararing active carbon using pulp
KR1019970026903A
Heating Appratus and Heating Method using Microwave
KR1020130110237A
Continuous operation method for microwave high-temperature pyrolysis of solid materials containing organic matter
KR1020210084593A
Method for preparing active carbon from lignin and polymer composites comprising active carbon prepared the same
KR1020210092392A
